Management of complex genital fistula: experience in a tertiary sub-Saharan hospital - Agwu, Ngwobia P.; Ahmed, Abdullahi A.; Muhammad, Abubakar S.; Mungadi, Ismaila A.; Oyibo, Emmanuel U.; Hassan, Mairo (International Surgery Journal, 2020)
Background: Management of complex genital fistulae is challenging due to the cost and technical skill required. This study reports our experience in the management of patients with complex genital fistulae and to highlight the crucial role of the reconstructive urologists. Methods: This was a retrospective review of female patients managed at a tertiary hospital in Nigeria from 2006 to 2017 for complex urinary fistulae. Data were extracted from patient case notes and the data analysed using the SPSS software. Results: Twenty-four female patients mean age 28.9±11.1 years. Fistulae resulted from prolonged obstructed labour 10 (41.6%), caesarean hysterectomy 7 (29.2%), caesarean section and abdominal hysterectomy 2 (8.4%) respectively. The fistulae were vesicovaginal 16 (66.7%), ureterovaginal 3 (12.5%). Others were vesicocutaneous, urethrovaginal and rectovaginal. Prior attempts at repair were done in 7 (29.2%) and the number of attempts ranged from 1 to 4. Surgical procedures included direct closure in 9 (37.5%), closure and uretero-neocystostomy 7 (29.2%), uretero-neocystostomy only 3 (12.5%) closure and abdominal hysterectomy 2 (8.3%), closure and continent catheterizable neo-bladder 2 (8.3%) and 1 (4.2%) closure, abdominal hysterectomy and uretero-neocystostomy. Post-operative complications were noted in 2 (8.3%) and consisted of gynaeatresia and recurrent RVF. Repair was successful in 70.8% of patients while failed repair was recorded in 16.7% and while stress incontinence was present in 12.5%. Conclusions: Complex genital fistulae in our practice are of obstetric origin involving the bladder, ureters and rectum. The reconstructive urologist has a crucial role the management for a favourable outcome.